Gender differences and stress management among psychology students - Alam Faizli, Hanisah; Rosli, Nur Aisyah; Mohd Zam, Nur Amirah; Bahrudin, Siti Suria; Mohd Mahudin, Nor Diana (2007)
This paper presents a study on gender differences in stress coping styles among psychology students in International Islamic University Malaysia. It is hypothesized that male respondents would be more likely to use problem-focused rather than emotion-focused coping style in dealing with stress as compared to the female respondents. A questionnaire consisted of 15 close-ended items was constructed and pilot-tested to 15 psychology students (7 males and 8 females). Minor changes were made after the pilot, and the actual survey was administered to 50 psychology students (25 males and 25 females). An analysis of variance of the data failed to support the hypothesis, with F (1, 48) = 3.273, p = .077. Justifications of the results in terms of overlapping roles and responsibilities for both males and females are discussed. Classification of items and more options for answers are suggested for future research.